1982
DOI: 10.1115/1.3266282
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Assessment of Wind Turbine Noise Generation

Abstract: The detailed analysis of a series of acoustic measurements taken near several large wind turbines (100 kWand above) IntroductionUntil the fall of 1979, noise from large wind turbines had not been a major concern. The situation changed however as the 2 MW, MOD-1 turbine installed near Boone, North Carolina began to undergo a series of operational tests which resulted in a number of sporadic and totally unexpected noise complaints from a few residents living within 3 km of the installation. Since that time, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Half of the measured room/wind turbine combinations actually demonstrated that the low-frequency limit of 20 dB set by Danish legislation was exceeded [32] . Furthermore, noise generated by wind turbines can lead to ground vibrations [68] , [71] . These ground vibrations are, however, small since walking or running 50 meters from the measurement point, elicited larger outdoor vibrations than a wind turbine located 90 meters away [68] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Half of the measured room/wind turbine combinations actually demonstrated that the low-frequency limit of 20 dB set by Danish legislation was exceeded [32] . Furthermore, noise generated by wind turbines can lead to ground vibrations [68] , [71] . These ground vibrations are, however, small since walking or running 50 meters from the measurement point, elicited larger outdoor vibrations than a wind turbine located 90 meters away [68] .…”
Section: Resultsmentioning
confidence: 99%
“…However, the perception of sound and sensation of airborne vibrations from i.e. wind turbines has been demonstrated to be higher indoor compared to outdoor and the vibrations indoor were detected as recurrent low-frequency pulses which are likely to be more annoying compared to a more constant noise [2] , [71] , [90] .…”
Section: Resultsmentioning
confidence: 99%
“…The power extracted from the wind is then proportional to P=QO (15) When the wind speed V w exceeds the cut-in speed V ci , the aerodynamic pitch angle is increased. The increase in angle of attack is then given by …”
Section: Power Output and Wind Speedmentioning
confidence: 99%
“…8 from the data of Ref. 26. These are estimated one-third octave band levels of vibrations which were judged perceptible in two different house structures excited by wind turbine noise.…”
Section: Vibration Perception Criteriamentioning
confidence: 99%